Screening for potential probiotic qualities of yeasts isolated from bahalina Tuba - Reli, Chris Miguel Y.; Lago, Catherine B. (2024)
Bahalina tuba is a traditional coconut wine beverage that is native to the eastern parts of the Philippines. It gets its distinct flavor from barok and the alcohol from spontaneous fermentation. Yeasts are microorganisms that performs spontaneous fermentations. The objectives of this study were to screen the probiotic potential of the yeasts isolated from bahalina tuba and characterize these isolates. Six bahalina tuba samples were collected and tested to determine if their alcohol content is within 10-13% that was established for bahalina tuba. All yeast isolates from bahalina tuba were tested for gastrointestinal survivability and hemolytic activity. The assimilation of carbon compounds, urea hydrolysis, and morphology were used to characterize the yeast isolates. The results showed that bahalina tuba samples had alcohol content that ranges from 10.58% to 11.7%. Twelve yeast cultures were isolated from bahalina tuba. All 12 yeast isolates did not show hemolytic activity; they are unable to lyse red blood cells. Moreover, all of the yeast isolates survived under simulated stomach and intestinal conditions, with survivability ranging from 26% to 55%. After characterization, two genera were found: putative Brettanomyces and putative Saccharomyces. This study showed that the yeasts isolated from bahalina tuba had the potential to be used as probiotics. However, more tests need to be conducted to confirm the probiotic qualities of the yeasts isolates. Identification of the yeast isolates to the species level is also necessary.
Undergraduate thesis (B.S. Biology) -- University of the Philippines, Tacloban.